Psychiatric morbidity among women with infertility in Pakistan: a cross-sectional survey - Carol Brayne; Samia Hussain (BMJ Open)
Objectives Although both infertility and mental illness are serious public health issues, relatively little is known about the mental health of women seeking fertility help in many lower and middle-income countries. This survey analyses the type of psychological burden that affects women who are unable to access in vitro fertilisation treatment (IVF), the risk factors for depression and anxiety among those seeking IVF treatment in Pakistan, and the existing mental health issues in women who seek help for the treatment of infertility to understand the accessibility and availability of specialist services. The aim of the study was to estimate the prevalence of depression among women seeking fertility treatments in three different settings at the same time.Design A cross-sectional survey with convenience sampling.Settings Different types of settings: private and public hospitals and traditional clinics in the community.Primary outcome measure Screening for depression using HADS (Hospital Anxiety and Depression Scale) and psychiatric interviews of those scoring above the cut-off level on HADS with WHO SCAN (Schedules for Clinical Assessment in Neuropsychiatry).Results The study sample consisted of 485 participants. The complete demographic data were available for 477 women. The HADS questionnaire was completed by 466 women, of whom 162 also completed the SCAN interview. Ages ranged from 15 to 60 years, with a mean age of 28.5 years, and 100% were married. According to HADS, 69% of cases of depression and anxiety were diagnosed, whereas 50% of those who were interviewed with SCAN had a diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), varying across settings (63% in government hospital, 42% traditional setting and 36% private hospital, respectively). There was a twofold risk of depression among the participants attending government hospitals (OR=2.4, CI=1.2, 4.7, p=0.03) as compared with women attending traditional clinics, and there was a slightly lower risk among the participants of private hospitals (OR=0.9, CI=0.4, 2.3, p=0.03) than other groups. The main risk factors found were having a traditional previous contact for treatment and attempting time (years). The HADS showed efficient performance with 97% sensitivity and 49% specificity with cut-off score 12. The main risk factors for depression were identified in those who had sought any previous treatment, having very low income and increased time spent attempting, with a clear difference in the risk of depression between those being treated at government hospitals and those following other treatment pathways.Conclusion In this study of women seeking infertility treatment in Pakistan, there was variation in the proportion meeting diagnostic criteria in different settings (as measured by HADS and WHO SCAN). This variation is likely to be due to the markedly different communities accessing the particular setting as well as the quality of treatment or help provided. It was clear overall that repeated attempts to seek help and length of trying are associated with higher prevalence of depression in this population. It is essential to provide appropriate and affordable fertility treatment in all government hospitals to ameliorate the effects of prolonged treatments and time spent struggling to reach places offering medical fertility care, and to introduce the concept of mental healthcare at fertility clinics within these government hospitals. The high risk of depression among the lower income group shows that providing access to specialist care and assisted reproduction to poor patients is urgently needed.